1972
DOI: 10.1080/01650527209360432
|View full text |Cite
|
Sign up to set email alerts
|

Corrected and supplemented descriptions of certain characoid fishes described by Henry W. Fowler, with revisions of several of their genera∗

Abstract: To cite this article: J. Géry (1972): Corrected and supplemented descriptions of certain characoid fishes described by Henry W. Fowler, with revisions of several of their genera , Studies on Neotropical Fauna, 7:1, 1-35

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
8

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 10 publications
0
15
0
8
Order By: Relevance
“…The monophyly of Hasemania, traditionally based mainly on the lack of an adipose fin, has been questioned by several authors (Böhlke, 1958;Géry, 1972Géry, , 1977Weitzman & Malabarba, 1999;Lima & Gerhard, 2001). However, preliminary results of a phylogenetic study of the genus ongoing by one of us (JPS) apparently suggest the group as monophyletic, based on a series of morphological characters.…”
Section: Discussionmentioning
confidence: 99%
“…The monophyly of Hasemania, traditionally based mainly on the lack of an adipose fin, has been questioned by several authors (Böhlke, 1958;Géry, 1972Géry, , 1977Weitzman & Malabarba, 1999;Lima & Gerhard, 2001). However, preliminary results of a phylogenetic study of the genus ongoing by one of us (JPS) apparently suggest the group as monophyletic, based on a series of morphological characters.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, examination of specimens originating from the region near the type locality, showed that meristic and morphometric data fall within the variation observed in the present study for G. gulo. Only data presented by Géry (1972) regarding number of teeth on the inner row of the premaxilla and number of maxillary teeth do not agree with the variation ranges observed during this study (3 vs. 2 and 31-36 vs. 35-55, respectively). Discrepancies in the number of premaxillary teeth are probably due to different ways of counting them (i.e.…”
Section: Geographic Variationmentioning
confidence: 36%
“…considering the canine teeth as part of the inner row or not). Regarding the maxillary teeth, it is common to find specimens with several fallen teeth, a fact that might have influenced the count reported by Géry (1972 Scale rows between dorsal-fin origin and lateral line 15-16 7…”
Section: Geographic Variationmentioning
confidence: 99%
See 2 more Smart Citations